Approaches to Forming Ethical Culture of Primary Class Students - Aziza Makhamatdonovna Mamatova (Web of Journals Publishing, 2023)
The article discusses approaches to the formation of the moral culture of elementary school students.
Keywords: learner, education, primary school, ethical culture, approaches, skills, competence.